Subjects of the application of special polygraphical knowledge in criminal proceedings - Pilyukov , Yurii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The purpose of the article. Definition of certain concepts and terms in polygraph activity. Outline of the list of subjects of the application of special polygraph knowledge and the study of the peculiarities of their main functions during the investigation of criminal offenses.The term «computer polygraph» should be understood as a special technical device that, according to its technical characteristics, registers changes in the physiological reactions of a physical person, which are the result of psychological processes, in response to the presentation of certain psychological stimuli using a special method.A polygraph examiner should be considered a specialist in cases where he meets the requirements of Art. 71 of the Criminal Procedure Code of Ukraine, according to which such a person must possess special knowledge in the field of polygraphology and can be involved by the parties to criminal proceedings during the pre-trial investigation and by the court during the trial to provide consultations, explanations, direct technical assistance, as well as drawing up reports and conclusions on issues related to his field of knowledge. Let’s consider in more detail the functions of the polygraph examiner engaged as a specialist.The subject of the application of special knowledge in the field of polygraphology, along with a specialist, also includes a forensic expert, a knowledgeable person who has the right to conduct a psychological examination with the use of a polygraph followed by drawing up an expert opinion, which, in accordance with Art. 84 of the Criminal Procedure Code, is one of the sources of evidence.Forensic psychological examination with the use of a polygraph is conducted by a forensic expert based on special knowledge in the field of polygraphology, the purpose of which is to identify the presence (or absence) in the memory of a sub-expert person of information that contains ideal traces (imaginary images) of past events.Conclusions. • The content of certain concepts and terms used in polygraph activity is formulated, in particular such as: «computer polygraph», «polygraph activity», «polygraph examiner», «specialist», «forensic expert», «polygraph examiner’s opinion» (specialist), «expert’s opinion», etc.• The list of subjects of application of special polygraph knowledge is outlined, which includes specialists and experts in this field. Peculiarities of their main functions during the investigation of criminal offenses were studied, in particular: provision of consultations; conducting psychophysiological surveys of persons with the use of a polygraph; drawing up reports and conclusions based on survey results; conducting psychological examinations.• It is substantiated that the most common reasons for the courts not to recognize evidence obtained with the help of a polygraph as admissible are the parties to criminal proceedings mistakenly identifying the conclusions of polygraph examiners (specialists) and the conclusions of experts, as well as the absence of supporting documents in the proceedings materials about the qualification of the subject of the application of special knowledge.